Size 48: a critical analysis of plus-size clothing patterns and their implications for body acceptance (ModaPalavra e-periódico, 2025)
This article investigates plus-size clothing pattern-making, focusing on size 48, and analyzes the ABNT guidelines applicable to this field, as well as the difficulties consumers face when searching for clothing that meets their physical and aesthetic needs. Based on authors such as Katz (2012) and Jimenez (2022), the study addresses concepts of representation and body acceptance, highlighting the importance of recognizing body diversity. The methodology is divided into two stages: the first compares size 48 measurement charts from four sources—Draft brand mannequins, WM Manequins, and the NBR 16933 guidelines for "spoon" and "rectangular" body types—while the second conducts a content analysis of an Instagram post by influencer Brenda Avelar, which promotes body acceptance and challenges traditional aesthetic standards, aligning with the empowerment and inclusion theories of Ribeiro and Matos (2022). The results indicate that, although efforts have been made to adjust the standards, ABNT guidelines still need improvements to accommodate a diverse audience, reinforcing the importance of considering the experiences of people with larger bodies. The research also reveals that the inclusion of plus-size bodies in the fashion market is not only a matter of representation but also an expanding market opportunity.
Keywords: plus size fashion; modeling; inclusion.